Flexible Transient Optical Waveguides and Surface‐Wave Biosensors Constructed from Monocrystalline Silicon. Issue 32 (26th June 2018) - Bai, Wubin; Yang, Hongjun; Ma, Yinji; Chen, Hao; Shin, Jiho; Liu, Yonghao; Yang, Quansan; Kandela, Irawati; Liu, Zhonghe; Kang, Seung‐Kyun; Wei, Chen; Haney, Chad R.; et al.
Abstract: Optical technologies offer important capabilities in both biological research and clinical care. Recent interest is in implantable devices that provide intimate optical coupling to biological tissues for a finite time period and then undergo full bioresorption into benign products, thereby serving as temporary implants for diagnosis and/or therapy. The results presented here establish a silicon‐based, bioresorbable photonic platform that relies on thin filaments of monocrystalline silicon encapsulated by polymers as flexible, transient optical waveguides for accurate light delivery and sensing at targeted sites in biological systems. Comprehensive studies of the mechanical and optical properties associated with bending and unfurling the waveguides from wafer‐scale sources of materials establish general guidelines in fabrication and design. Monitoring biochemical species such as glucose and tracking physiological parameters such as oxygen saturation using near‐infrared spectroscopic methods demonstrate modes of utility in biomedicine. These concepts provide versatile capabilities in biomedical diagnosis, therapy, deep‐tissue imaging, and surgery, and suggest a broad range of opportunities for silicon photonics in bioresorbable technologies. Abstract : Flexible, transient optical waveguides constructed from monocrystalline silicon enable precise delivery of light to targeted biological tissues, at dimensions that can approach those of a single cell, then undergo controlled bioresorption into benign products after a well‐defined operational time, thereby serving as building blocks for silicon‐based bioresorbable photonic systems, with potential broad applicability in diagnosis and therapy.